2021
DOI: 10.1016/j.diabres.2021.108670
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota thrombus colonization may influence athero-thrombosis in hyperglycemic patients with ST segment elevation myocardialinfarction (STEMI). Marianella study

Abstract: Objectives. We examined the association of the coronary thrombus microbiota and relative metabolites with major adverse cardiovascular events (MACE) in hyperglycemic patients with ST segment elevation myocardial infarction (STEMI).Background. Hyperglycemia during STEMI may affect both development and progression of coronary thrombus via gut and thrombus microbiota modi cations.Methods. We undertook an observational cohort study of 146 rst STEMI patients treated with primary percutaneous coronary intervention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…There are several eligible pathophysiological mechanisms potentially mediating a causal relationship. On the one hand, hyperglycemia during the AMI is supposed to be a main determinant of atherosclerotic plaque instability and rupture [ 5 ] and furthermore affects coronary thrombus composition [ 6 ] and increase coronary thrombus burden via thrombus microbiota dysbiosis [ 26 ]. On the other hand, hyperglycemia might exhibit sympathetic over-activity with a hyperglycemia-mediated proinflammatory pathway and in this affecting outcome [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several eligible pathophysiological mechanisms potentially mediating a causal relationship. On the one hand, hyperglycemia during the AMI is supposed to be a main determinant of atherosclerotic plaque instability and rupture [ 5 ] and furthermore affects coronary thrombus composition [ 6 ] and increase coronary thrombus burden via thrombus microbiota dysbiosis [ 26 ]. On the other hand, hyperglycemia might exhibit sympathetic over-activity with a hyperglycemia-mediated proinflammatory pathway and in this affecting outcome [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To relate these effects more closely to our study, the TMAO levels are also influenced by the diet and by the secondary effects on the microbiome [37]; however, little effect was observed on the TMAO levels [38]. On this note, it has only recently been shown that higher contents of Prevotella in hyperglycemic coronary are associated with high thrombus burden and TMAO in hyperglycemic patients [39].…”
Section: Mitigation Of Adverse Effects Related To Cardiovascular Diseasesmentioning
confidence: 61%
“…The relative abundance changes of Prevotella were reported to injure the colonic epithelia, resulting in inflammation and thus inflammatory cytokine generation like IL-6, TNF-a, and IL-8 ( Xia et al, 2021 ). It is also related to TMAO production ( Sardu et al, 2021 ). Oscillibacter ( Chen et al, 2020 ; Dessì et al, 2021 ), Roseburia ( Cornuault et al, 2020 ), Bacteroides ( Yuan et al, 2021 ), Paraprevotella ( Fei et al, 2019 ; Zhang X. et al, 2021 ), Phascolarctobacterium ( Pan et al, 2021 ), and Intestinimonas ( Afouda et al, 2019 ; Luo et al, 2021 ) exert promoting effects in the SCFA generation or associate positively with its content.…”
Section: Disscussionmentioning
confidence: 99%